Entrepreneurship for the poor in developing countries - Yoonyoung Cho (IZA World of Labor, 2015)
Can entrepreneurship programs be successful labor market policies for the poor? A large share of workers in developing countries are self-employed in low-paying work or engage in low-return entrepreneurial activities that keep these workers in poverty. Entrepreneurship programs provide business training and access to finance, advisory, and networking services with the aim of boosting workers' earnings and reducing poverty. Programs vary in design, which can affect their impact on outcomes. Recent studies have identified some promising approaches that are yielding positive results, such as combining training and financial support.
Keywords: J24; O12; J46; 330; small-scale entrepreneurship; self-employment; livelihoods